Grenada : Sixth Review Under the Extended Credit Facility Arrangement and Financing Assurances Review-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Grenada's Sixth Review under the Extended Credit Facility (ECF) Arrangement and Financing Assurances Review. The government met all continuous and end-December 2016 performance criteria and structural benchmarks. The economy grew by about 3.9 percent in 2016, reflecting continued strong construction activity and steady external demand for Grenada's tourism services. The pace of restructuring of public debt has accelerated in recent months, and Grenada's debt-to-GDP ratio declined to 83.4 percent at the end of 2016 from 108 percent in 2013. The IMF staff supports the completion of the Sixth Review under the ECF arrangement and the financing assurances review.